Prototype of Integrated National Identity Storage Security System in Indonesia using Blockchain Technology - Fathiyana, Rana Zaini; Yutia, Syifa Nurgaida; Hidayat, Dinda Jaelani (JOIV : International Journal on Informatics Visualization, 2022)
Approximately 29 institutions in Indonesia issue were identifying numbers, such as ID cards, driving licenses, BPJS, etcetera. In general, the identity storage system is designed with a centralized system and managed by each government agency. However, this system has some disadvantages, like data replication and redundancy. Furthermore, the Indonesian government is now undertaking a program through the Ministry of Home Affairs to use population data for public services by providing access to organizations cooperating for population data use. With a centralized database managed by a single entity, data abuse can occur and rely on third parties, the sole authority of the national identity data. The blockchain-based solution described in this paper to integrate a national identity system can provide the advantages of a population data utilization program. The system designed can facilitate convenience in sharing and updating population data while also ensuring the security and integrity of the population data. The citizens do not have to worry about the possibility of data misuse by user institutions. Blockchain technology offers decentralization through the participation of members across a distributed network. There is no single point of failure, and no single user may alter the transaction record. Our proposed approach could help the government of Indonesia secure citizens' private information and increase transparency in information management.